Autorregulação e Comércio Internacional: do percurso teórico à demonstração empírica - Farenzena, Suélen (Universidade do Vale do Rio dos Sinos, 2013)
This assignment aims to highlight the autonomy and capacity for self-regulation more and more social segments, assuming the hypothesis that, although the law from the state remains as a basic reference for ordinary citizens, in practice it suffers from competition other guidelines, as such, should be recognized and respected. Therefore, it seeks to analyze, in the first chapter, the issue concerning globalization, starting from the conception of paradox and to autopoiesis, with these subsidies, consider polycentrism, while overcoming regional limitations and global constitution of autonomus sectors . In this line, the next topic notes the necessity to be launched by a new look on legal pluralism, working with the idea of hypercomplexity and contextualizations diversity on intention to reconstruct the evolutionary course of this institute until the sign of governance. Prudentially, with the unveiling of the theoretical trajectory of social autonomy, the second part of the study, in it's first item, delineates, then, the question of legal regulation, demonstrating the ndispensability of a structure of law that respects the very capacity of society, represented by issue of civil constitutions and organizations. As a paradigmatic illustration of this context and reflective role that fits right in at this juncture, it remains stated,by withering, in the last chapter, per interviews with professionals from large companies, scholars and members of assembly, the international commerce, with emphasis on the role of international contracts while elements of interaction arising from the order structuring, which refer to conflicts denouement by the proper sector.
Keywords: Globalização policêntrica; Pluralismo jurídico transnacional; Organização setorial; Comércio internacional; Polycentric globalization; Transnational legal pluralism; Sector organization; International commerce; ACCNPQ::Ciências Sociais Aplicadas::Direito